'They point guns for money, we run the country!': Provincial modernities in Hatke cinema. Issue 2 (1st October 2013) - Paul, Arunima
Much recent scholarship on post-liberalization Indian cinema has explored the ways in which its productions have participated in or pushed back against the ideological project of neo-liberal transformation. Significantly, both kinds of critical endeavours have focused on genres depicting the metropolis and its rich cinematic figures (the new creative hero, the psychotic hero, the tapori, the metrosexual) as the locus of the elaboration and exploration of modernity. Recent 'hatke' cinema or the growing body of films addressing the domestic cosmopolitan, which are distinctive (or 'hatke') in their formal and thematic innovativeness, realism and indie-style; has also been the subject of these critical enquiries. This article examines two films from within the landscape of hatke cinema that depict northern Indian provincial youth: Tigmanshu Dhulia's Haasil (2003) and Kabeer Kaushik's Sehar (2005). Popular and critical discussions of these films have located their 'hatke' quotient in their 'deglam' depictions of university politics, student politicians, hostel cultures and provincial youth's sense of disaffection. In this article I argue that the provincial youth-film troubles binaristic notions of the metropolitan as the site of India's global modernity and the provincial hinterland as entrapped by age-old structures of caste and feudalism. Through its exploration of caste-masculinities in the mundane spaces of a provincial small-town (rather than the aspirational horizons of Indian or global metropolises), the genre registers what I call 'provincial modernities' as a complex of the intertwined colonial, postcolonial and neo-liberal histories of the developmental project and power. In these films, the figure of the youth political-entrepreneur through his occupation of the discrete spaces of the provincial university campus (corridors, classrooms, hostels), and his subsequent infiltration of economically burgeoning sections of the city (railway contracting, real estate, telecommunications), illuminates a long provincial history of the bourgeois nation-state, crony capitalism and subsequent transformations wrought by economic liberalization and the democratization of caste. In doing so, I argue, the films posit the provincial as another site of impact as well as formulation of contemporary modernity and its inequities.